1903 N.J. Laws 337-38 - (:unkn) unknown (My University, 1903)
Ch. 169, 1: It shall not be lawful to sell, barter, exchange, hire or loan to any person under the age of fifteen years, any gun, pistol, toy pistol, or other firearms, or for any person under the age of fifteen years to purchase, barter or exchange any gun, pistol, toy pistol or other firearms, nor for any person under the age of fifteen years to carry, fire or use a gun, pistol toy pistol or other firearms, except in the presence of his father or guardian, or for the purpose of military drill in accordance with the rules of a school; it shall be the duty of all persons selling, hiring, bartering or exchanging pistols, revolvers, guns or other firearms, to keep and maintain a book of registry of the same
Keywords: POSSESSION - MINORS; REGISTRATION; TRANSFER - MINORS